2001
DOI: 10.1677/joe.0.1710119
|View full text |Cite
|
Sign up to set email alerts
|

The fourth International Standard for Human Urinary FSH and LH: specificities of LH seminal vesicle weight gain assays in the collaborative study differ between laboratories

Abstract: The fourth International Standard for Human Urinary FSH and LH (IS; in ampoules coded 98/704) was compared with the third International Standard for Urinary FSH and LH (IS 71/264) by 10 laboratories in nine countries, using FSH and LH in vivo bioassays.Estimates of the FSH content of the IS by augmented ovarian weight gain assays were homogeneous within each laboratory and over all laboratories. The combined weighted geometric mean estimate of FSH content of the IS (with 95% fiducial limits) in terms of IS 71/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Analysis of ancillary variables may nevertheless provide indications of variables that could be relevant in future research. For example, the study by Storring and Gaines Das (2001) suggested that the exact age of the rats used in those experiments may be a more critical variable than had previously been recognized, and that this factor may also be strain dependent to some extent, even though these questions were not directly addressed by that study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Analysis of ancillary variables may nevertheless provide indications of variables that could be relevant in future research. For example, the study by Storring and Gaines Das (2001) suggested that the exact age of the rats used in those experiments may be a more critical variable than had previously been recognized, and that this factor may also be strain dependent to some extent, even though these questions were not directly addressed by that study.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study (Storring and Gaines Das 2001) in which ovarian weight relative to body weight was measured in rats as response to follicle stimulating hormone, body weights and organ weights were also reported separately for many experiments. A marked outlying response was detected in one experiment in which weights of the 48 female rats were within the range 73 to 90 g with the exception of one, which was reported as 58 g. When the data were analyzed, it could no longer be determined whether this was a recording error; however, the difference was so extreme that it was omitted from analysis.…”
Section: Use Of Ancillary Variables To Detect Outliersmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institute of Biological Standards and Controls (NIBSC) Urinary Follicle Stimulating Hormone and Urinary Luteinizing Hormone, 4 th International Standard, NIBSC Code: 98/704 (NIBSC, Herts, UK) reference standard was prepared for each replicate assay by dissolving a single vial (FSH assay) or two vials (LH assay) each with 1.0 ml sterile saline solution and subsequently pooled, in the case of the latter. By definition of the World Health Organization Expert Committee on Biological Standardization, the NIBSC 98/704 standard contains 72 IU of urinary FSH and 70 IU of urinary LH per ampoule [ 18 ]. The NIBSC 98/704 standard was used because a similar standard was not available for a combination of recombinant FSH and recombinant LH.…”
Section: Methodsmentioning
confidence: 99%
“…horas ("overnight") a 37 °C com 5 M ácido acético e aplicando o produto da reação de dissociação diretamente na RP-HPLC (Carvalho, 2009). (Storring, 2001).…”
Section: Dissociação Do Heterodímerounclassified